Akta Pengakuan Utang Sebagai Pengganti Bukti Penyetoran Modal Dalam Pendirian Perseroan Terbatas - Zharfani, Nadhira Faza; Teddy Anggoro (UNES Law Review, 2024)
In practice, there are often disobedient shareholders who do not deposit the full capital that has been issued, even though their names as shareholders have been recorded in the Company's deed of establishment. In this research, the author raises the case of a Deed of Acknowledgement of Indebtedness made by a shareholder at PT This research will discuss the absence of capital deposits by shareholders in the establishment of a limited liability company which can be said to be a debt based on the applicable laws and regulations, as well as reviewing whether a Deed of Acknowledgement of Indebtedness can be used as a substitute for proof of capital deposits in the Company. This research was prepared using normative juridical research methods, utilizing document studies using secondary data, and using analytical descriptive research specifications, and analyzed using qualitative analysis methods. The research results show that the absence of a full deposit made by shareholders in the Company constitutes a debt and/or obligation and is considered fulfilled if the shareholder has made a full deposit into the Company. Apart from that, as reflected in Article 33 paragraph (2) of Law no. 40/2007, shareholders are required to deposit capital in full to the Company as proof of legal ownership of the issued shares. Thus, the Deed of Acknowledgment of Indebtedness made by the shareholder in the case raised serves as evidence of an Authentic Deed which strengthens and justifies the Company's position in postponing the granting of shareholder rights to shareholders who have not paid for the shares that have not been deposited. However, the existence of the Deed of Acknowledgment of Indebtedness cannot replace proof of capital deposit in the Company.